An Analysis on the Spread Mooring of the Belida FSO Induced by Squall Loads - Murdjito, M; Pravitasari, Inneke Yulistanty; Djatmiko, Eko Budi (Department of Naval Architecture - Diponegoro University, 2020)
Squall is the occurrence of a sudden sharp increase in wind speed, thus amplifies sea environmental loads. In the South of Natuna Sea, squall can reach an intensity of up to 50 m/s or close to 100 knots. In this water, the Belida FSO operates at a water depth of 77.0 m, tethered to the seabed by a spread mooring system. Squall’s impacts on the FSO mooring system has been examined by implementing time-domain simulations accommodated in a numerical model based on the 3-D wave diffraction theory. The simulations were performed by varying the squall duration of escalation, i.e. 2.5, 5.0, and 10.0 minutes, for the load cases of 1-year extreme operational and 100-year extreme survival conditions propagating at 0°, 45°, 90°, 135°, 180°. The three squall durations of escalation substantially increase the significant wave height Hs by averagely 60%, 50% and 34%, respectively. The largest of the maximum mooring tension due to the sea load directions is found to be brought about the 45° load when magnified by the squall with a 2.5-minute duration of escalation. In this respect, the largest intensities of the operational and survival tension loads may reach some 2,027 kN and 3,318 kN, respectively, which are eventually far below the MBL of 7,685 kN. The largest x-axis offsets in operational and survival conditions are 3.94 m and 10.21 m, respectively. Whereas the largest y-axis offsets for operational and survival loads are found to be 13.31 m and 15.48 m. These y-axis offset intensities are larger than the limiting criteria, i.e. 15% of the water depth or 11.55 m.